2017
DOI: 10.1097/mou.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy as metastasis-directed therapy for oligometastatic prostate cancer

Abstract: Based on data from retrospective studies, progression-free survival following MDT for oligometastatic PCa is promising with few adverse events. Comparative prospective studies are under way and will shed light on the future of MDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…When one compares the present SLND cohort to groups who studied explicitly patients staged with PSMA PET/CT, one-year progression-free survival (PFS) ranged from 23 to 64%, with higher PFS found in patients with a radio-guided SLND approach [4,[28][29][30] indicating that this might further allow the dissection of affected lymph nodes that had not been visualized beforehand on PET/CT. Overall, bRFS of the present SLND cohort compares nicely to this range and similar PFS ranges are known for SBRT cohorts [5].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…When one compares the present SLND cohort to groups who studied explicitly patients staged with PSMA PET/CT, one-year progression-free survival (PFS) ranged from 23 to 64%, with higher PFS found in patients with a radio-guided SLND approach [4,[28][29][30] indicating that this might further allow the dissection of affected lymph nodes that had not been visualized beforehand on PET/CT. Overall, bRFS of the present SLND cohort compares nicely to this range and similar PFS ranges are known for SBRT cohorts [5].…”
Section: Discussionsupporting
confidence: 76%
“…Likewise, few studies on SLNRT were identified in a recent review: Patients with pelvic and/or extra-pelvic nodes were either treated by stereotactic body radiotherapy (SBRT) (55%) or elective nodal radiotherapy (ENRT) (45%) to a lymph node region or the whole pelvic lymphatic pathways [5]. In patients treated with ENRT 3-year progression-free survival ranged from 61.8 to 75% [6], whereas in patients with SBRT to PET-positive lymph nodes 3-year progression-free survival ranged between 26 and 33% [5]. This is strikingly comparable to outcome data achieved by SLND, although one has to reconsider that the majority of patients in the reported studies were staged at best with choline positron emission tomography/computer tomography (PET/CT) thus underestimating the true extent of nodal recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Benefit is primarily gained in patients treated for multiple lymph node oligometastases: geometrical deformations are accounted for, dose can be delivered in one plan and margins can be reduced. In recent years stereotactic body radiation therapy (SBRT) has become the standard treatment option for the treatment of patients with lymph node oligometastases in many centers [1,2]. SBRT allows for the delivery of a relatively high amount of dose in few fractions with a very steep dose gradient [3] and is often given to postpone the start of systematic therapy and improve progression-free or overall survival without compromising the quality of life [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in treating oligorecurrent patients with a metastasis-directed approach aiming to postpone disease progression and the need for definitive, palliative ADT. Metastasis-directed therapy (MDT) by means of surgery or radiotherapy has already been widely evaluated in several retrospective analyses [3,4]. To date, only one prospective randomized trial, the Surveillance or Metastasis-Directed Therapy for Oligometastatic Prostate Cancer Recurrence (STOMP) trial, evaluated the effect of MDT versus surveillance in PCa [5], where MDT was either performed via surgery or via stereotactic body radiotherapy (SBRT) to the metastatic lesion(s).…”
Section: Introductionmentioning
confidence: 99%